Higgs interference effects in top-quark pair production in the 1HSM - Banfi, Andrea; Kauer, Nikolas; Lind, Alexander; Lindert, Jonas M.; Wood, Ryan (The journal of high energy physics, 2024)
A bstract We present a next-to-leading-order (NLO) study of the process pp ( → { h 1 , h 2 }) → t t ¯ + X in the 1-Higgs-singlet extension of the Standard Model with an additional heavy Higgs boson h 2 that mixes with the light Higgs boson h 1 . This process is subject to large interference effects between loop-induced Higgs-mediated amplitudes and the QCD continuum background which tend to overcompensate any resonance contributions. A reliable modelling of the resulting top-pair invariant mass shapes requires the inclusion of higher-order QCD corrections, which are presented here. The computation of these NLO corrections is exact in all contributions but in the class of non-factorisable two-loop diagrams which are included in an approximate way such that all infrared singular limits are preserved. We present numerical results for several benchmark points with heavy Higgs masses in the range 700–3000 GeV considering the production of stable top quarks. We find that the interference effects dominate the BSM signal yielding sharp dip structures instead of resonance peaks. The significance and excludability of the BSM effect is explored for the LHC Run 2, Run 3 and HL-LHC.